FAKTOR-FAKTOR YANG MEMENGARUHI CALVING INTERVAL SAPI KRUI DI KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT - Atha Nadhila Rosa; Madi Hartono; Sri Suharyati; Siswanto Siswanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
Research on calving interval of Krui cattle in Pesisir Selatan District was held on December 2019 until January 2020 with 142 Krui cattle who have given birth more than once and had been inseminated belong to 68 farmers. The purpose of this reserch were to know: 1) calving interval of Krui cattle in Pesisir Selatan District, 2) the factors and magnitude of the factors which disturb calving interval of Krui cattle in Pesisir Selatan District. This research used census method, data obtained was real data that present and accurate in Pesisir Selatan District. Data was analysed by multiple linear regression with SPSS (Statistics Packet for Social Science) program. The results showed that calving interval of Krui cattle in Pesisir Selatan District was 12,53±1,42 month. Factors that affected the value of calving interval in Krui cattle in Pesisir Selatan District were derived from the mating partus that positively associated with factor value of 0,769 and the S/C that positively associated with factor value of 0,912. Keywords : Calving interval, Krui cattle, Pesisir Selatan District